Experimental analysis for performance of concrete with addition of steel fibres, SBR and polypropylene fibres - Pathan, Mohd. Gulfam; Wankhade, Rajan L.; Shende, A.M.; Swaroop, Ajay; Mashaan, Nuha (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sufficient experimentation is observed in literature to examine the brittle behaviour of concrete. Presently, addition of different modified polymer and fibres can be treated as an effective way for improving the behaviour of concrete. Steel fibres are now generally mixed with concrete as because of such fibres sufficient strengths are gained. Fibre Reinforced Concrete acquires high stiffness, strength and durability subjected to different environment. In this experimental investigation it is mixed steel fibres with concrete with various percentages (0.35% to 0.85%) with addition of Polypropylene fibre. The primary objective is first to check whether the employment of steel fibres allows the improvement in strength. Next objective is to verify the effect of a mixing of steel fibres and modified polymer namely SBR. The third objective of the present study deals with the combination of steel fibres with synthetic polypropylene fibres in varying percentages. Preparation of specimen is performed in lab for different contents% of styrene butadiene rubber polymer with the hooked end SF. The experimental program includes cube, cylinder and beam specimens with fabricated in 1% to 10% steel fibres. Further 15% modified polymer-SBR is added in the different mixes. After this 0.15% to 0.25% polypropylene is mixed to M30 and M40 grade of concrete. The volume fraction for fibre having 100 kg/m3 of steel fibres (1.27% Vf) may be effectively employed. It is seen that by varying the %contents of SF’s and SBR; strong bond is developed leading to bridge of micro cracks by the polypropylene in RC members.